Long juvenility trait: A vehicle for commercial utilization of soybean (Glycine max) in lower latitudes. (3rd June 2021) - Gupta, Sanjay; Agrawal, Nisha; Tripathi, Rachana; Kumawat, Giriraj; Nataraj, Vennampally; Maranna, Shivakumar; Satpute, Gyanesh K.; Ratnaparkhe, Milind B.; Rajesh, Vangala; Chandra, Subhash; Jain, Meeta
Abstract: Soybean, a short‐day plant, has its origin in higher latitudes of China, and its commercial cultivation remained confined to areas >22°N till 1970s due to precocious flowering accompanied with reduced biomass in lower latitudes. This review summarizes the effect of short days on soybean phenology, discovery of a novel long juvenile (LJ) trait, its role in breaking the latitudinal boundary for soybean production, identification of genes and impact of LJ trait on world soybean production. E6, J and E9 major genes governing the trait have been characterized and cloned. LJ varieties are late in flowering and maturity and successful in long rainfall regime of Brazil. Availability of vast vacant fallows of Cerrado has been another factor for utilization of this trait in Brazil. Recent advances for developing short‐duration LJ varieties, for limited rainfall areas and its suitability to existing cropping systems by combining it with photoinsensitivity, have been reviewed. Based on the available data from lower latitudes of Brazil, the contribution of the LJ trait is estimated to 23.7% of the total world production.